Power flow control and small-signal stability analysis considering the SSSC facts - Pupin, Carlos Eduardo; Fortes, Elenilson V.; de Araujo, Percival Bueno [UNESP]; Macedo, Leonardo H. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2021)
This paper presents a model for the static synchronous series compensator (SSSC) taking into account its real aspects and internal dynamics, and incorporates it into both the power flow formulation and the power sensitivity model for small-signal stability analysis. For the small-signal stability analysis, the power system stabilizer and power oscillation damping supplementary controllers are coupled to the generators and the SSSC, respectively, to damp the electromechanical oscillations present in the power system. The parameters of the supplementary controllers are tuned using the residue method. Simulations are performed using the New England 39-bus test system and the results indicate that the proposed formulation for the SSSC is effective for both power flow and small-signal stability analyses. Besides that, it is verified that the supplementary controllers, together with the SSSC, are efficient to damp the low-frequency oscillating modes present in the power system.
Keywords: FACTS; Power flow; Power sensitivity model; Residue method; Small-signal stability; SSSC